ANALISIS KINERJA KEUANGAN DAN PERUBAHAN STRUKTUR PELAPORAN PDAM TIRTA KHATULISTIWA KOTA PONTIANAK SETELAH PENERAPAN SAK ETAP - B51111012, Ersy Rusdiyanti (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
BUMN is a realization of state investment in the business world. the purpose is to encourage and develop the national economy activity. BUMD in this case, it is not much different from the purpose BUMN, only difference lies in the ownership which in the context of countries and regions. One of the enterprises that are undertaking a strategic role in the region is PDAM. In this case, PDAM Tirta Khatulistiwa Pontianak is one business unit belongs to the area qualifies as an entity that does not have significant public accountability so that the financial statements prepared or presented must use a standard of financial accounting entities without public accountability (SAK ETAP). The purpose of this research is to gain understanding of whether there is an increased performance of the company and whether there are changes in the reporting structure after application of SAK ETAP of PDAM. This study used a qualitative descriptive study. The steps taken to obtain data and information is to use the method of documentation. These results indicate that (1) The financial performance of of PDAM after three trends were analyzed using the ratio indicates that the financial condition of the period after the adoption of SAK ETAP better than before application of SAK ETAP, although the increase is not significant. (2) There are quite a lot of changes in the reporting structure in profit / loss, and balance sheet, while the statement of changes in equity and cash flow unchanged. Keywords: Â financial Â performance, financial statements, standard of financial accounting entities without public accountability (SAK ETAP).